RECENTING ADVANCE REPORT IN TCP COGESTION CONTROL USING AIMD - Kalai Selvi, S; Meena, A (International Journal of Computer Sciences and Engineering, 2014)
In this paper introduced a common report of TCP congestion control and using the fast transmit over sending packets of Using AIMD Additive increase and multiplicative decrease. The host receives implicit packet loss or explicit packet mark indicate internal congestion. Concept implements AIMD to prevent from the traffic over TCP network. The acknowledgment of PACKET SENDING implements faster over TCP network using AIMD. Recent the report using Active queue management AQM has the pathological packet-dropping pattern.